Conflict transformation for sustainable Christian marriage - Afolaranmi, A.O. (Acta Theologica, 2022)
IbukunOluwa, J. & IbukunOluwa, R. (Ibadan, Nigeria: Simplex Creations, 2022). pp. 76. ISBN: 978-978-59646-0-8 (paperback). Price: 1000 Nigerian Naira.